Functional Literacy Level of Officials in Selected Barangays: Basis for an Extension Project - Galang, Ruby T.; Arrozal, Jocelyn Y.; Cortez, Leila L.; Regala, Angelo D. (Future Science / FSH-PH Publications, 2025)
This research investigates the functional literacy levels of barangay officials in selected agricultural communities within Guagua, Pampanga, aiming to design an extension program that improves governance effectiveness. Employing a quantitative descriptive design, the study utilizes a modified DepEd-ALS functional literacy test to evaluate reading, writing, and numeracy competencies among 30 elected officials across Ascomo, Pulungmasle, and Maquiapo. The findings reveal a significant gap between academic qualifications and practical literacy skills, with over 36% of respondents classified at the beginning literacy level. This underscores the need for targeted interventions, especially in remote areas with limited access to education. The study contextualizes functional literacy as a pivotal element for public service delivery, transparency, and civic engagement. Results show that while 80% of respondents attained college education, their functional abilities in written communication, budgeting, and digital tasks vary significantly. The proposed extension program is a six-week, module-based training covering reading, writing, numeracy, communication, and digital literacy. Recommendations include integrating technological tools, routine assessments, and peer mentorship to sustain improvements. Ultimately, enhancing functional literacy is framed not just as a personal upgrade for officials, but as a foundational strategy for community empowerment, responsive governance, and sustainable development.